Efeito de biofertilizante inoculante de Bacillus subtilis e Trichoderma spp. em áreas de cultivo agrícola no município de Nova Tebas - Paraná - Freitas, Caio Evandro Santos de (2017)
The cropping systems with applications of synthetic inputs used by current agriculture alter important soil attributes that are regulated by biota, besides causing several problems related to the environment and public health, being of extreme importance the substitution by organic inputs, such as Biofertilizers. The objective of this work was to evaluate the effect of the application of biofertilizer in the microbiological community of the soil in agricultural areas with the use of biofertilizers made from Bacillus subtilis bacteria and fungi species of the genus Trichoderma spp.. This study was developed In private rural property in the municipality of Nova Tebas, Parana. Six sample sites were demarcated and three subsamples were collected each, homogenized, totalizing one sample per sample site, three control sampling sites and three biofertilizer treated. The samples were then taken to the Ecology Laboratory of the Federal Technological University of Paraná, Campus Campo Mourão, for processing. In the laboratory, removal of unwanted materials and sieving were performed. Then, for moisture stabilization, the soil was weighed every 24 hours until water loss. Subsequently, the samples were serially diluted and plated in duplicate. From the statistical analyzes carried out with the number of colony forming units per gram of soil (CFU/g), it was concluded that the biofertilizer resulted in a significant microbiological evolution of the soil in the treated areas, mainly at the end of the experiment, after one hundred and thirty-five days of application of the biofertilizer, showing a greater microbiological density.